The Civic Duty to Report Crime and Corruption - Delmas, Candice (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique de l’Université de Montréal, 2014)
Is the civic duty to report crime and corruption a genuine moral duty? After clarifying the nature of the duty, I consider a couple of negative answers to the question, and turn to an attractive and commonly held view, according to which this civic duty is a genuine moral duty. On this view, crime and corruption threaten political stability, and citizens have a moral duty to report crime and corruption to the government in order to help the government’s law enforcement efforts. The resulting duty is triply general in that it applies to everyone, everywhere, and covers all criminal and corrupt activity. In this paper, I challenge the general scope of this argument. I argue that that the civic duty to report crime and corruption to the authorities is much narrower than the government claims and people might think, for it only arises when the state (i) condemns genuine wrongdoing and serious ethical offenses as “crime” and “corruption,” and (ii) constitutes a dependable “disclosure recipient,” showing the will and power to hold wrongdoers accountable. I further defend a robust duty to directly report to the public—one that is weightier and wider than people usually assume. When condition (ii) fails to obtain, I submit, citizens are released of the duty to report crime and corruption to the authorities, but are bound to report to the public, even when the denunciation targets the government and is risky or illegal.